Recoil in vacuum for Te ions: Calibration, models, and applications to radioactive-beam g-factor measurements - Stuchbery, A; Stone, N (2007)
In the light of new g factor results for the stable isotopes between 122Te and 130Te, the calibration and modeling of the recoil-in-vacuum (RIV) interaction for Te ions is reexamined, and the recent radioactive-beam g factor measurement on 132Te by the RIV technique is reevaluated. The implications for further RIV g-factor measurements in the 132Sn region are discussed. © 2007 The American Physical Society.